Impacto de la especialización productiva manufacturera en la convergencia económica provincial en Ecuador, periodo 2008-2020: mediante técnicas econométricas con datos panel - Cajamarca Ramon, Alejandrina Amelia (2022)
Guayas and Pichincha have been the main economic centers of Ecuador and have maintained high production throughout the last two decades. However, the other provinces have also shown significant variations in their production and this has been strongly characterized by activities related to the tertiary and secondary sector. In this line, for 2019 according to the Maritime Chamber of Ecuador, the manufacturing sector in the country moved 35.6% of the national production. The objective of this research was to analyze the impact of manufacturing productive specialization on provincial economic convergence in Ecuador from 2018 to 2020 by using econometric techniques with panel data, to determine public policy proposals for the production. The results show that at the provincial level there is a process of divergence, contrary to the relationship suggested in the empirical studies of Sala-Martin, which suggests an inverse relationship between the growth rate and income; this result indicates an increase in inequalities and poverty. However, he presence of manufacturing productive specialization shows a positive impact on the convergence process, in which growth rates tend to be steady state. In this context, it is expected that the richer economies will become richer and the poorer economies poorer. In view of this situation, it is feasible that the Ministry of Production, Foreign Trade, Investment and Fisheries should resume and implement the Basic Industries Plan and promote provincial development poles.